2006
DOI: 10.1007/s00705-006-0823-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence supporting the confirmation of Maracuja mosaic virus as a species of the genus Tobamovirus and production of an infectious cDNA transcript

Abstract: The complete genome sequence of maracuja mosaic virus (MarMV) was determined and analyzed. The full MarMV genome consisted of 6794 nucleotides, and this is the largest genome size among known tobamoviruses. The MarMV genome RNA contained four open reading frames (ORFs) coding for proteins of M(r) 126, 181, 34 and 18 kDa from the 5' to 3' end, respectively. The lengths of the 5' nontranslated region (NTR) and the 3' NTR were 54 and 177 nucleotides, respectively. Phylogenetic tree analysis revealed that these Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Song et al [15] suggested the existence of a sixth subgroup in the genus Tobamovirus isolated from the Passifloraceae, based on the phylogenetic analysis of the four tobamovirus proteins. Here, according to the phylogenetic analyses and the hosts from which the viruses were originally isolated, the presently available 32 tobamoviruses could be divided into at least eight subgroups, Solanaceae-, Brassicaceae-, Cactaceae-, Apocynaceae-, Cucurbitaceae-, Malvaceae-, Leguminosae-, and Passifloraceae-infecting subgroups based on both the complete nucleotide sequences and 126 kDa, 54 kDa, MP and CP amino acid sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al [15] suggested the existence of a sixth subgroup in the genus Tobamovirus isolated from the Passifloraceae, based on the phylogenetic analysis of the four tobamovirus proteins. Here, according to the phylogenetic analyses and the hosts from which the viruses were originally isolated, the presently available 32 tobamoviruses could be divided into at least eight subgroups, Solanaceae-, Brassicaceae-, Cactaceae-, Apocynaceae-, Cucurbitaceae-, Malvaceae-, Leguminosae-, and Passifloraceae-infecting subgroups based on both the complete nucleotide sequences and 126 kDa, 54 kDa, MP and CP amino acid sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Min and co-workers [14] proposed that tobamoviruses could be divided into at least five subgroups according to the amino acid composition and primary structure of their CPs, and the hosts from which the viruses were originally isolated. Song et al [15] suggested tobamoviruses should be divided into six subgroups based on the phylogenetic analysis of the four tobamovirus proteins with the existence of passifloraceae-infecting subgroup in the genus Tobamovirus .…”
Section: Introductionmentioning
confidence: 99%
“…The OAs of viruses from subgroup 3 are also located in the MP ORF; however, the MP and CP ORFs overlap by 77 nt, and members of this subgroup are able to infect both Solanaceae and Brassicaceae species. Isolation of new tobamoviruses, such as frangipani mosaic virus (Lim et al, 2010), maracuja mosaic virus (Song et al, 2006), passion fruit mosaic virus (Song and Ryu, 2011), cactus mild mottle virus (Min et al, 2006) and rattail cactus necrosis-associated virus (Kim et al, 2012), along with the complete sequencing of their genomes, showed that MP/CP overlap is not unique to Brassicaceae- infecting tobamoviruses but is also present in Apocynaceae -, Passifloraceae -, and Cactaceae -infecting viruses (Figure 1). …”
Section: ′-Terminal Gene Overlap and Tobamovirus Classificationmentioning
confidence: 99%
“…Tobamoviruses have been classified into different groups based on host range, coat protein structure, serological relationships and genome organization [2,10,11,[16][17][18]21], and their evolution of has been comprehensively reviewed [3,11,13,16,23]. The genus Tobamovirus contains 22 definitive and one tentative species [10] and is divided into three subgroups based on natural host range, genomic organization and phylogenetic clustering [10,11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Tobamovirus contains 22 definitive and one tentative species [10] and is divided into three subgroups based on natural host range, genomic organization and phylogenetic clustering [10,11,16,17]. However some authors propose five subgroups of tobamoviruses, infecting members of the families Brassicaceae, Cactaceae, Cucurbitaceae, Malvaceae, and Solanaceae/Orchidaceae, based on the primary structure of the coat protein, serological specificity and host range [2,18], while Song et al [21] have proposed a sixth subgroup of tobamoviruses infecting members of the family Passifloraceae. A recent analysis of tobamovirus sequences by Adams et al [1] describing the family Virgaviridae has highlighted some incorrectly labelled sequences in that genus.…”
Section: Introductionmentioning
confidence: 99%